Biodegradation of the nitrile-containing insecticides sulfoxaflor, flonicamid, thiacloprid, and acetamiprid by immobilized Escherichia coli harboring genes of nitrile hydratase and a cobalt transporter. Issue 2 (April 2023) - Jiang, Huoyong; Li, Huaxiao; Wang, Yuhe; Yu, Xuexiu; Chen, Xiaoyue; Dai, Yijun
Abstract: The nitrile-containing insecticides sulfoxaflor, flonicamid, thiacloprid, and acetamiprid are used widely in agriculture, polluting the environment and harming animals. The Co 2+ -dependent enzyme nitrile hydratase (NHase) is a powerful tool for the degradation of nitrile-containing insecticides. Here, the NHase activities of Escherichia coli pET28a- Ps NHase, harboring Pseudomonas stutzeri CGMCC 22915 ( Ps ) NHase gene, and E. coli pET28a- Ps NHase- Ps CbiM, harboring genes of Ps NHase and a cobalt transporter Ps CbiM, were compared. The presence of Ps CbiM promoted Ps NHase activity. E. coli pET28a- Ps NHase- Ps CbiM was immobilized using calcium alginate, which increased the tolerance of its NHase to acidic, alkaline, and high-temperature environments. Immobilized E. coli pET28a- Ps NHase- Ps CbiM was applied to degrade sulfoxaflor, flonicamid, thiacloprid, and acetamiprid. These insecticides were both substrates and inhibitors of immobilized E. coli pET28a- Ps NHase- Ps CbiM. Substrate inhibition model assays showed that the optimum initial concentrations of sulfoxaflor, flonicamid, thiacloprid, and acetamiprid for degradation by immobilized cells were 455.01, 195.50, 139.20, and 410.26 μmol/L, respectively. Degradation of nitrile-containing insecticides by immobilized engineered E. coli cells was reported here for the first time. This study provides a novel and excellent bioremediation agent for treatment of wastewater contaminated with nitrile-containing insecticides. Graphical Abstract: ga1 Highlights: Nitrile-containing insecticides were degraded by immobilized engineering E. coli . The degradation activity of immobilized cells was inhibited by high concentrations of insecticides. Cell immobilization increased the tolerance of its NHase to environmental stress. Ps CbiM transport Co 2+ to Ps NHase and promoted its activity. Ps CbiM had less than 30 % amino acid sequence similarity to other Co 2+ transporters.